The value of emotional intelligence for high performance coaching - A commentary - Fox, A. (International Journal of Sports Science and Coaching, 2011)
Strong EI appears to enhance the leader-follower relationship. Thus, it seems obvious that a coach with such abilities would connect better with their staff/team/athletes to produce high performance. Nevertheless, the real-world application of EI (or emotional expertise/people skills) and leading people effectively is not straightforward, and often a juggling act of competing responsibilities/expectations. Therefore, we advocate that coach education/accreditation might consider the development of abilities beyond technical and tactical knowledge. Ultimately, sport coaching is more than just the instruction of skills and drills, and central to their role, coaches lead and manage the production of high performance. Thus, coach education/accreditation should be encouraged to emphasise formal and informal training/modules not just on EI and sports leadership, but other skills central to their role, such as, how to lead, inspire, and enhance motivation, or how a culture of excellence might be developed.